Some Manifestations of Vindictive Behavior in Pedagogical Discourse - Sergey A. Zavrazhin; Marina M. Fomina (National Research Mordova State University, 2021)
Introduction. The problem of vindictive behavior in modern pedagogy is poorly studied both at the theoretical and empirical level. It is only indirectly touched on in studies on disciplinary measures in the educational environment, the prevention of non-normative activity of children.The aim of the research is to learn the genesis of the problematization of vindictive activity in a pedagogical format, as well as to study experimentally the features of vindictiveness of at-risk adolescents. Materials and Methods. The empirical part of the article highlights the results of an experiment to detect the features of vindictiveness in adolescents at risk using a questionnaire and diagnostics of the "Scale of resentment and vindictiveness" (E. P. Ilyin, P. A. Kovalev). 50 people took part in the survey. The authorʼs questionnaire includes an associative experiment to determine the semantic field of the concept of vindictiveness and a method for analyzing situations. The questionnaire "Scale of resentment and vindictiveness" involves determining a personʼs tendency to hostility through resentment and vindictiveness, by collecting questionnaire data-responses. Results. According to the results of an empirical study, it was revealed that the vindictive activity of adolescents in the social risk group is a form of manifestation of frustration-driven conscious hidden aggression. In general, adolescents of the risk group are characterized by a high level of vindictiveness; gender differences in the description of the phenomenon are determined: underage students of rehabilitation centers are more prone to resentment, while male students are more prone to hostility. Discussion and Сonclusion. The obtained results contribute to the development of the ideas about the determination of the vindictive behavior of minors in the social risk group, enrich pedagogical knowledge with the methodology for identifying destructive forms of establishing justice in young people.